The arts of cover music album as a branding tool / Nazirul Munir Mohd Jamel - Mohd Jamel, Nazirul Munir (2014)
According to (Dalrymple, Jr., 2009) Judging a Book by its Album Cover: A Study of the Relationship Between Musical Preference and Personality, he stated that, "Despite the prevalence of television and the Internet, music still holds an important share of popular media. It is clear that music remains a meaningful part of the lives of people of all ages". This statement couldn't be disagreed anymore but the problem that needs to study is the relationship between music and visual art. Is they're a people really listening into music without see the video clip, the identity, fashion or cover album. This needs to be on research of how the relationship between sound and word can visualize into artwork? What is concept of form in music? Music gave the influence of art entity in communication. What are the music meaning in certain part of rhythm attack, melancholy, the solo, the storyline ofthe lyric and the interpretation ofthe vocals? Basically the fans of the certain genre will know what is the artwork presents the music they are like. The violence image of skulls or Mohawk it could be related to the punk or heavy metal band. The image ofself-portrait it can be relate to pop artist. But are this is really present of what the meaning behind the album philosophy? How far is the artist's understanding of the artwork in album can be a platform for the marketing? The album's artwork is the first impression of people to buy music album. From the history of conceptual album, Pink Floyd and The Beatles, they are aware in presenting the album's artwork and relate to the music that they are playing.